Successful Application of the Mast Cell Activation Test in Immediate Hypersensitivity to Amoxicillin - Céspedes, Jose A.; Lebrón-Martín, Clara; Vallecillos-Azor, Lucía; Torres, Pablo; Tesfaye Ayane, Amene; Bogas, Gádor; Salas, María; Ariza, Adriana; Montañez-Vega, María Isabel; Torres, María José; Mayorga, Cristobalina (Wiley, 2026)
ABSTRACT Background Immediate drug allergic reactions (IDAR) to betalactams are frequent, yet mislabelling remains common and negatively impacts clinical decisions. Conventional diagnostics such as STs and drug provocation are effective but limited by time, risk, and contraindications in severe cases. In vitro alternatives—sIgEquantification and basophil activation tests (BAT)—offer safer options, although performance may be affected by biological variability and suboptimal sensitivity with an important drawback for the latter in patients with non-releaser basophils. This study aimed to evaluate a mast cell activation test (MAT) based on human CD34+-derived mast cells (dMCs) for IDAR diagnosis to amoxicillin (AX) using both free AX and dendrimeric amoxicilloyl conjugates (G4/G5-AXO). Methods CD34+ cells were cultured for 10–12 weeks to generate dMCs. After passive sensitization with sera from AX-allergic patients (N = 28) or tolerant controls (N = 11), dMCs were stimulated with free AX, G4-AXO, or G5-AXO. Activation was quantified by CD63 expression via flow cytometry. Diagnostic performance was compared with BAT and sIgE determination by ImmunoCAP. Results MAT with free AX achieved 53.57% sensitivity, G4/G5-AXO reached 46.43%, and all methods maintained 100% specificity. Combining results with AX or dendrimeric stimuli increased sensitivity to 75% while preserving specificity. Importantly, MAT identified positive cases among BAT non-releasers and patients with undetectable sIgE. Conclusions Under optimized conditions, MAT using dMCs and different AX determinants reached 75% sensitivity and 100% specificity. The complementary use of free AX and dendrimeric conjugates expands detection across heterogeneous IgE reactivity profiles from AX-allergic patients, reinforcing the diagnostic value of advanced cellular models and engineered allergens.
Keywords: Alergia a los medicamentos; Basophil activation test; Drug allergy; IgE; In vitro test; Mast cell activation test